Impacts of performing electrolysis during organocatalyzed atom transfer radical polymerization. Issue 31 (7th July 2020) - Corbin, Daniel A.; McCarthy, Blaine G.; Miyake, Garret M.
Abstract : An electrochemical variant of organocatalyzed atom transfer radical polymerization (O-ATRP) is developed and investigated. Abstract : An electrochemical variant of organocatalyzed atom transfer radical polymerization (O-ATRP) is developed and investigated. Inspired by electrochemically mediated atom transfer radical polymerization (eATRP), potentiostatic electrolysis is used to manipulate the catalyst's redox states in O-ATRP to understand whether deactivation in O-ATRP can be enhanced to improve polymerization control. During the course of this work, several possible side reactions are investigated, and the electrochemical apparatus is optimized to reduce side reactions at the counter electrode. This electrochemically modified O-ATRP method (eO-ATRP) is then studied at different applied potentials, under different irradiation conditions, and with two photoredox catalysts to understand the impact of electrolysis on polymerization control. Ultimately, although electrolysis was successfully used to improve polymerization control in O-ATRP, some additional challenges have been identified. Several key questions are postulated to guide future work in this area.